The Role of Hypoxia on the Neuronal Differentiation of Gingival Mesenchymal Stem Cells: A Transcriptional Study. Issue 5 (May 2019) - Gugliandolo, Agnese; Diomede, Francesca; Scionti, Domenico; Bramanti, Placido; Trubiani, Oriana; Mazzon, Emanuela
Mesenchymal stem cells (MSCs) are widely used in stem cell therapy for regenerative purposes. Oral-derived MSCs, such as gingival MSCs (GMSCs), deriving from the neural crest seem more suitable to differentiate toward the neuronal lineage. In addition, the preconditioning of MSCs may improve their beneficial effects. Since it is known that hypoxia may influence stem cell properties, we were interested in evaluating the effects of hypoxia preconditioning on the neuronal differentiation of GMSCs. With this aim, we evaluated the transcriptional profile of GMSCs exposed to basal and neuroinductive medium both in normoxia and in cells preconditioned for 48 h in hypoxia. We compared their transcriptional profile using Next Generation Sequencing. At first we observed that hypoxia did not alter cell morphology compared with the GMSCs cultured in a normoxic condition. In order to understand hypoxia preconditioning effects on neuronal differentiation, we screened genes with Log2 fold change ≥2 using the database Cortecon, that collects gene expression data set of in vitro corticogenesis. We observed that hypoxia preconditioning induced the expression of more genes associated with different stages of cortical development. The common genes, expressed both in normoxia and hypoxia preconditioning, were involved in developmental and neuronal processes. Interestingly, a larger number of genes associated with development biology and neuronal process was expressed in GMSCs differentiated after hypoxia preconditioning compared with those in normoxia. In addition, hypoxic-preconditioned differentiated GMSCs showed a higher expression of nestin, PAX6, and GAP43. Our data demonstrated that hypoxia preconditioning enhanced the differentiation potential of GMSCs and induced the activation of a higher number of genes associated with neuronal development. In conclusion, hypoxia may be used to improve MSCs' properties for stem cell therapy.